Impact of thyroid autoimmunity and vitamin D on in vitro fertilization/intracytoplasmic sperm injection outcomes among women with normal thyroid function - Liu, Yalong; He, Zining; Huang, Ning; Zeng, Lin; Wang, Yang; Li, Rong; Chi, Hongbin (Frontiers in Endocrinology, 2023)
This prospective cohort study aimed to determine the impact of thyroid autoimmunity and total 25-hydroxyvitamin D concentration on early pregnancy outcomes in women undergoing in vitro fertilisation/intracytoplasmic sperm injection. The study included 1,297 women who underwent in vitro fertilisation/intracytoplasmic sperm injection cycles. The study endpoints were clinical pregnancy, ongoing pregnancy, ectopic pregnancy, and early miscarriage rates. Our study found that the total 25-hydroxyvitamin D serum concentrations (P<0.001) and anti-Mullerian hormone levels (P=0.019) among patients in the TAI group were lower than those in the non-TAI group. Additionally, the study population in each group was divided into three subgroups according to the total vitamin D status based on clinical practice guidelines (deficient, <20 ng/mL; insufficient, 21–29 ng/mL; and sufficient, ≥30 ng/mL). In the TAI group, the number of good-quality embryos decreased in patients with vitamin D deficiency (P=0.007). Logistic regression analysis indicated that ageing prevented women from achieving clinical (P=0.024) and ongoing pregnancy (P=0.026). The current findings suggest that patients with TAI had reduced serum vitamin D concentration. Furthermore, in the TAI group, the number of good-quality embryos decreased in patients with vitamin D deficiency. Finally, ageing adversely impacted achieving clinical and ongoing pregnancy.